The Effect of Ca Content on CaO-Zeolite on Nitrogen Adsorption Capacity - Nasikin, Mohammad; Utami, Tania Surya; Siahaan, Agustina TP (Makara Journal of Technology, 2002)
In industry, Ca zeolite is used as nitrogen selective adsorbent with the use of PSA (Pressure Swing Adsorption)/VSA (Vacuum Swing Adsorption) methods. Natural zeolite modified to be Cao-zeolite by ion exchange process using Ca(OH)2. Adsorption test was done on CaO-zeolite with different Ca concentration to understand how it’s adsorption phenomena on oxygen and nitrogen. Adsorption test has been done for CaO-zeolite with Ca concentration = 0,682%, 0,849% and 1,244% to oxygen and nitrogen with equal concentration seperately. Pressure variation has being done three times (5 minutes long each time) adsorption time to analyze the connection between adsorption time and how many moles of nitrogen and oxygen being adsorbed. Adsorption test showed that there is a limit of Ca concentration to make CaO-zeolite more selective to adsorb nitrogen. CaO-zeolite with Ca concentration . 1,125% adsorb nitrogen more selective than oxygen. Because the nitrogen content in air is four times the oxygen so we can conclude that the air adsorption rate by zeolite will be four times the adsorption rate by oxygen. This differences in adsorption rate will make the use for CaO-zeolite as a oxygen enrichment equipment possible.